The effects of a four week balance training programme on dynamic balance among handball players in Sekolah Menengah Kebangsaan Alam Megah 2 / Muhammad Syukuri Mazlan - Mazlan, Muhammad Syukuri (Faculty of Education, 2014)
A high performance athlete should have an excellent health related physical fitness and a tremendous skill related physical fitness despite of discipline and emotionally wise. One of the components of the skill related physical fitness is the balance. The component of balance in every athlete is very important for each coach to be stressed about. In this simple research, the researcher will provide proven about the vitality of having balance in sports to an athlete. This study was apparently the first attempt to study the effects of balance training program on dynamic balance among handball players. The 30 research participants were purposively sampling from Sekolah Menengah Kebangsaan Alam Megah 2 handball players to ensure the research participants was equal during the beginning of the test since the research participants had received equal training frequency and protocols. Participants will be tested by using Johnson Modification of the Bass Test of Dynamic Balance (JMBT) on early of the month and four weeks after the first test. As a result, there are no significant differences in dynamic balance between the two groups (control group and experimental group), (t = 1.189, df= 28, p> .05).